INCREASING THE CAPACITY OF FISHERMEN IN HANDLING DROWNING VICTIMS IN THE COASTAL BEACH AREA - Dewi, Yulis Setiya; Zulkarnain, Hakim; Kurniawati, Ninuk Dian; Sriyono, Sriyono; wahyuni, Erna Dwi; Qona'ah, Arina; Maropi, Anuchit (Universitas Airlangga, 2025)
Introduction: Fishermen often face extreme climates and weather that are life-threatening when at sea. The lack of knowledge of fishermen about first aid for drowning victims can increase the death rate due to drowning. This community service activity aimed to increase the knowledge and skills of fishermen in providing first aid to drowning victims. Methods: This community service was carried out on 30 fishermen who live in the Coastal Area of Paciran Village, Lamongan Regency. The method used is through education and training which includes health promotion and training for drowning victims. Education activities are carried out directly to fishermen with the theme of handling drowning victims. The training materials provided to fishermen are basic life support and handling choking victims. The training is carried out through lectures, demonstrations - simulations and discussions. Results: Fishermen's knowledge before the activity was 6 people (20%) in the poor category, 10 people (33.3%) in the sufficient category, and 14 people (46.7%) in the good category. While knowledge after the activity 1 person (3.3%) had poor knowledge, 2 people (6.7%) in the sufficient category, and 27 people (90%) in the good category. The pre-test and post-test results showed an increase in fishermen's knowledge about first aid for drowning victims. Conclusion: Increasing the capacity of fishermen in providing first aid to drowning victims can be done through health education and training. Training activities can be integrated into fishermen's programs or activities so that fishermen's capacity will be more optimal.